Preparation method of bacillus licheniformis modified steel slag and application of bacillus licheniformis modified steel slag in preparation of recycled concrete

Through the preparation method of Bacillus licheniformis modified steel slag, the surface of the steel slag is modified by using stearic acid and silane coupling agent to form a hydrophobic coating and enhance the bonding effect, which solves the problem of water absorption and expansion of steel slag in rainy and snowy weather, and significantly improves the mechanical properties and service life of recycled concrete.

CN119638239APending Publication Date: 2025-03-18TAIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510064938.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Steel slag is prone to absorb water and expand in rainy and snowy weather, resulting in damage to concrete structures, reducing service life, and limiting the application of steel slag in engineering.

Method used

The preparation method of Bacillus licheniformis modified steel slag is adopted, and the steel slag is modified by combining stearic acid and silane coupling agent to form a hydrophobic coating and enhance the bonding effect, inhibit the volume expansion of the steel slag, and the modified steel slag is used as a microbial carrier to improve the survival life of microorganisms and the strength of concrete.

Benefits of technology

It significantly reduces the pore volume of recycled concrete, improves the pore structure, improves the compactness, compressive and tensile strength, and extends the service life of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638239A_ABST
    Figure CN119638239A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of bacillus licheniformis modified steel slag and application of the bacillus licheniformis modified steel slag in preparation of recycled concrete, and the preparation method is characterized by comprising the following steps: soaking steel slag in a stearic acid solution, stirring, performing vacuum drying, continuously soaking the steel slag in a silane coupling agent solution, stirring, and performing vacuum drying to obtain the modified steel slag, and dipping the modified steel slag in the bacillus licheniformis suspension, taking out the modified steel slag, vacuumizing for adsorption, dipping the modified steel slag in the bacillus licheniformis suspension, taking out the modified steel slag, and drying the modified steel slag to constant weight to obtain the bacillus licheniformis modified steel slag. The recycled concrete is prepared by mixing the bacillus licheniformis modified steel slag, cement, sand, water, recycled aggregate, the bacillus licheniformis modified steel slag, calcium acetate, aluminum oxide and urea in proportion, and has the advantages that the volume expansion of the steel slag is inhibited, the pore volume of the recycled concrete is remarkably reduced, the pore structure is improved, and the strength of the recycled concrete is improved. The compactness, the compression resistance and the tensile strength of the recycled concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and in particular relates to a method for preparing steel slag modified by Bacillus licheniformis and application of the steel slag in preparing recycled concrete. Background Art

[0002] Steel slag is a byproduct produced during the steelmaking process, and its main components include CaO, MgO, SiO2, Al2O3 and Fe2O3. The utilization rate of steel slag in China is only 29.5%, resulting in a stockpile of more than 1.8 billion tons of steel slag. The accumulation of steel slag not only occupies a large amount of land resources, but also produces dust, pollutes the air, and causes serious damage to the environment. At present, in order to actively implement the policy of energy conservation and emission reduction and promote resource recycling, steel slag has been widely used and actively tried in many fields. Among them, in cement production, steel slag, as one of the raw materials of slag cement, can improve the strength and durability of cement; in addition, the alkaline properties of steel slag make it have application potential in wastewater treatment, especially in removing heavy metals from water and neutralizing acidic wastewater; steel slag is also used in soil improvement and slag fertilizer, which helps to improve soil fertility and regulate soil pH; however, the most prominent is that in road engineering, steel slag is used as roadbed and pavement base materials, and its high compressive strength, wear resistance and impact resistance make it an ideal construction material. However, steel slag has a porous surface structure and contains excessive free calcium oxide (f-CaO) and free magnesium oxide (f-MgO), which easily absorbs water and expands in rainy and snowy weather. This will cause serious damage to the concrete filled with steel slag, reduce the service life of the structure, and limit the application of steel slag in engineering.

[0003] At present, the surface treatment methods for steel slag include aging treatment, accelerated carbonization treatment and surface modification treatment. The aging treatment method releases the expansion potential of the steel slag before it is used by promoting the hydration of f-CaO and f-MgO, thereby alleviating the volume expansion of the steel slag in the later stage. However, the aging treatment is inefficient, and the steel slag occupies a large area. Long-term static treatment will cause great pollution to the environment. The accelerated carbonization treatment of steel slag is a method in which CO2 reacts with active substances such as f-CaO and f-MgO in the steel slag under specific temperature, humidity, CO2 concentration and pressure conditions, thereby eliminating f-CaO and f-MgO to reduce the expansion of the steel slag. However, the accelerated carbonization of steel slag requires specific process conditions (such as high concentration of CO2 gas, suitable temperature and humidity), the operation is complicated, and the requirements for equipment and operating environment are high, which will incur a large cost. Common surface modification methods inhibit the hydration of f-CaO and f-MgO by forming a water-proof structure on the surface of steel slag, such as using inorganic materials such as cement and fly ash to wrap steel slag and inhibit its volume expansion by filling the pores of steel slag; or using organic materials such as polyvinyl alcohol (PVA) and epoxy acrylic silicone resin (EAOR) to treat the surface of steel slag. The above methods can solidify the liquid hydrophobic coating on the surface of steel slag to form a continuous film, effectively close the pores on the surface of steel slag, and block the contact between the active components inside the steel slag and water, thereby effectively inhibiting the volume expansion of steel slag. However, the rough surface of steel slag is filled and leveled after surface treatment, which weakens the mechanical bite force and interfacial bonding strength between steel slag and cement mortar, and the hydrophobic film hinders the hydration of mineral components inside the steel slag. The reduction of hydration products will have a certain negative impact on the strength of the steel slag mixture.

[0004] Specific types of microorganisms are added to concrete materials to repair concrete cracks by using cell metabolism to produce calcium carbonate (CaCO3) mineral precipitates. At the same time, a more compact concrete material can be obtained. Compared with other traditional concrete crack repair methods, biomineralization produces fewer harmful substances and less pollution to the environment, making it a green repair that is beneficial to the environment. In addition, when cracks reappear, microorganisms can be "activated" by external stimuli, and can continue to complete targeted self-healing repairs through mineralization. Since this repair automatically repairs microcracks without any human intervention and can reduce maintenance costs, microbial mineralization self-repair plays a vital role in concrete repair. However, since the pH value of concrete after hydration of ordinary Portland cement is about 13, although the optimal pH value of bacteria depends on the type of strain, the activity of bacteria gradually decreases with the increase of alkalinity. Another aspect is that cement hydration causes the pore size to decrease, compressing the living space of microorganisms and causing the spore activity to gradually lose. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a preparation method of Bacillus licheniformis modified steel slag which can inhibit the volume expansion of steel slag and improve the mechanical properties of steel slag, and its application in the preparation of recycled concrete. The Bacillus licheniformis modified steel slag significantly reduces the pore volume of the recycled concrete, improves the pore structure, and improves the density, compressive resistance and tensile strength of the recycled concrete.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing steel slag modified by Bacillus licheniformis, comprising the following steps:

[0007] Step 1: Preparation of modified steel slag

[0008] The steel slag is immersed in a stearic acid solution, stirred at a speed of 400-800 rad / min for 20-40 minutes by a high-speed disperser, and then placed in a vacuum drying oven at 45-55° C. for 6-10 hours. After the sample is cooled to room temperature, it is further immersed in a silane coupling agent solution, stirred at a speed of 400-800 rad / min for 20-40 minutes by a high-speed disperser again, and then placed in a vacuum drying oven at 45-55° C. for 6-10 hours to obtain a modified steel slag;

[0009] Step 2: Preparation of steel slag modified by Bacillus licheniformis

[0010] The modified steel slag obtained in the step is sieved by a shaking screen to select the modified steel slag with a particle size of 4.75-9.5 mm as a carrier material, immersed in a Bacillus licheniformis suspension for 20-60 minutes, taken out and placed in a vacuum machine for vacuuming, adsorbed at a pressure of -0.1 MPa for 20-60 minutes, immersed in the Bacillus licheniformis suspension for 20-60 minutes, and then filtered to remove excess impregnation liquid, and dried at 25-45° C. to constant weight to obtain Bacillus licheniformis modified steel slag.

[0011] Furthermore, the preparation method of the stearic acid solution is as follows: add stearic acid to ethanol, and stir evenly at 400-600 rpm at 40-50° C. using a magnetic stirrer to obtain a stearic acid solution with a mass concentration of 1%.

[0012] Furthermore, the preparation method of the silane coupling agent solution is as follows: after mixing the silane coupling agent, water and ethanol in a volume ratio of 3:47:50, stirring at a speed of 100-300 rpm for 30-60 minutes at room temperature until the solution is transparent without obvious particles or precipitation, the silane coupling agent solution is obtained.

[0013] Furthermore, the preparation method of the Bacillus licheniformis suspension is as follows: transfer the freeze-dried powder of Bacillus licheniformis into a solid culture medium for activation, select the activated strain and inoculate it into a liquid culture medium, and culture it in a constant temperature shaking incubator at 25-35°C for 20-28h, the pH value is 7-11, the inoculation amount is 4% by volume, and when the OD of the strain in the culture medium is 600 When the value reaches 1.75, Bacillus licheniformis suspension is obtained.

[0014] Furthermore, the preparation method of the solid culture medium is as follows: 10g of peptone, 5g of sodium chloride, 3g of beef extract, and 20g of agar are dissolved in 1L of distilled water, sterilized in an autoclave at 121°C, and then the pH is adjusted to 10-12 with a Na(OH)2 solution. The preparation method of the liquid culture medium is as follows: 10g of peptone, 5g of sodium chloride, and 3g of beef extract are dissolved in 1L of distilled water, and then sterilized in an autoclave at 121°C.

[0015] The present invention also provides Bacillus licheniformis modified steel slag recycled concrete obtained by the preparation method. The concrete is composed of the following raw materials and their weight proportions: 300-400 parts by weight of cement, 700-800 parts by weight of sand, 150-200 parts by weight of water, 700-800 parts by weight of 9.5-19 mm recycled aggregate, 100-200 parts by weight of 4.75-9.5 mm recycled aggregate, 200-300 parts by weight of Bacillus licheniformis modified steel slag, 5-20 parts by weight of calcium acetate, 40-50 parts by weight of aluminum oxide and 2-18 parts by weight of urea.

[0016] Preferably, it is composed of the following raw materials and their weight parts: 384 weight parts of cement, 731.04 weight parts of sand, 187.92 weight parts of water, 731.28 weight parts of 9.5-19 mm recycled aggregate, 125.76 weight parts of 4.75-9.5 mm recycled aggregate, 240 weight parts of Bacillus licheniformis modified steel slag, 17.83 weight parts of calcium acetate, 48 weight parts of alumina, and 10.16 weight parts of urea.

[0017] Compared with the prior art, the advantages of the present invention are: the preparation method of steel slag modified by Bacillus licheniformis and its application in preparing recycled concrete, the steel slag is modified by stearic acid and silane coupling agent, on the one hand, a hydrophobic coating is formed on the surface of the steel slag by stearic acid, the wettability of the steel slag surface is reduced, and the penetration of external water is significantly reduced, thereby inhibiting the volume expansion of the steel slag; on the other hand, the silane coupling agent is used as a binder for stearic acid and cement mortar, which improves the bonding and bite effect of the modified steel slag and cement mortar, and increases the overall strength of the mixture. Using porous steel slag as a carrier "protective cover" for microorganisms not only provides a relatively stable living space for microorganisms, significantly improves the survival life of microorganisms, and due to its porous characteristics, it can also provide microorganisms with the water and nutrients needed for survival, while having no obvious effect on the strength of concrete, and can improve the utilization rate of steel slag resources and improve the mechanical properties of recycled concrete. Furthermore, Bacillus licheniformis modified steel slag is used in the preparation of recycled concrete, so that the Bacillus licheniformis and modified steel slag have a synergistic effect, which significantly improves the compressive and tensile strengths of the recycled concrete. The Bacillus licheniformis modified steel slag significantly reduces the pore volume of the recycled concrete, improves the pore structure, and increases the density of the recycled concrete. At the same time, this modification technology performs better in the later stage of maintenance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The results of water absorption of different types of slag are shown in Figure 2.

[0019] Figure 2 The results of the water expansion rate determination of different slag types at different immersion times;

[0020] Figure 3 The water contact angle measurement results of different slag types;

[0021] Figure 4 The results of compressive strength test of different recycled concrete at different ages;

[0022] Figure 5 The results of tensile strength test of different recycled concrete at different ages;

[0023] Figure 6 These are the pore volume measurement results of recycled concrete at different ages and with different pore sizes. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below with reference to the accompanying drawings.

[0025] 1. Experimental Materials

[0026] Recycled aggregate: The coarse aggregate used is recycled coarse aggregate after crushing, with a particle size range of 4.75-19.5mm and good particle grading. The performance indicators of recycled aggregate for concrete are tested with reference to the standard experimental method of Pebbles and Crushed Stone for Construction (GB / T 14685-2022).

[0027] Steel slag: Steel slag aged for more than one year is selected, and the average expansion rate is about 1.08%, which is less than the 2% required by the specification. The steel slag with a particle size of 4.75-9.5mm is screened out by a shaking screen machine, and then used after cleaning and drying. Its physical composition is shown in Table 1 below.

[0028] Table 1 Test results of slag physical properties

[0029]

[0030] Cement: The present invention uses P·O 42.5R ordinary Portland cement. To ensure the working performance of the material, various indicators of the test cement are tested in accordance with the "Standard Specification for Portland Cement" (ASTM C150 / C150 M-22), "Standard Test Method for Chemical Analysis of Hydraulic Cement" (ASTM C114-22) and other standard specifications. The physical and chemical components of the cement are shown in Tables 2 and 3.

[0031] Table 2 Chemical mineral composition of cement

[0032]

[0033] Table 3 Physical properties of cement

[0034]

[0035] Preparation of stearic acid solution: Stearic acid was added to ethanol, and stirred evenly at 45° C. and 500 rpm using a magnetic stirrer to obtain a stearic acid solution with a mass concentration of 1%.

[0036] Preparation of silane coupling agent solution: Mix silane coupling agent, water and ethanol in a volume ratio of 3:47:50, and stir at 200rpm for 30-60 minutes at room temperature until the solution is transparent without obvious particles or precipitation. This is the silane coupling agent solution. Use ethanol as a solvent to enhance solubility and avoid too fast hydrolysis of the silane coupling agent.

[0037] Preparation of Bacillus licheniformis suspension: Bacillus licheniformis lyophilized powder (Beina Bio, strain number BNCC335814) was selected for Bacillus licheniformis. The lyophilized powder was first transferred into a solid culture medium (prepared in a 10g peptone, 5g sodium chloride, 3g beef extract, and 20g agar dissolved in 1L distilled water, sterilized in a 121°C autoclave, and then adjusted to pH 10-12 with a Na(OH)2 solution) for activation. The activated strain was selected and inoculated into a liquid culture medium (prepared in a 10g peptone, 5g sodium chloride, and 3g beef extract dissolved in 1L distilled water, sterilized in a 121°C autoclave) for culture. The successfully inoculated bacteria were cultured in a constant temperature shaking incubator at 30°C for 20-28h and a pH value of 7-11. The inoculation amount was 4% by volume. When the bacterial solution OD 600 When the value reaches 1.75, the culture solution is taken to obtain the Bacillus licheniformis suspension.

[0038] Other materials: Since adding a proper amount of alumina is beneficial to lowering the internal pH value of concrete, 2-8% of alumina by mass is added in this test to enable Bacillus licheniformis to survive and grow better. This test uses calcium acetate and urea as nutrients for the mineralization reaction of Bacillus licheniformis. The fine aggregate used in this test is natural river sand. According to the specification "Construction Sand" (GB / T 14684-2022), the fineness modulus of the sand is 2.9, which belongs to the medium sand in Zone II. 2. Specific embodiments

[0040] Example 1: Preparation of steel slag recycled concrete modified by Bacillus chlamydosus, comprising the following steps:

[0041] Step 1: Modified steel slag

[0042] The surface of steel slag was modified by a combination of stearic acid and silane coupling agent, and the surface of steel slag was modified by immersion method. First, the steel slag was immersed in the prepared stearic acid solution and stirred at a speed of 600 rad / min for 30 minutes using a high-speed disperser to improve the contact between the modifier and the steel slag; then, the steel slag was placed in a vacuum drying oven and dried at 50°C for 8 hours. After the sample cooled to room temperature, it was immersed in the silane coupling agent solution and stirred at a speed of 600 rad / min for 30 minutes using a high-speed disperser again; then, the steel slag was placed in a vacuum drying oven and dried at 50°C for 8 hours to remove the residual solvent and ensure the complete completion of the surface modification process of the steel slag. It should be noted that in this study, stearic acid and silane coupling agent were used to modify steel slag. On the one hand, stearic acid formed a hydrophobic coating on the surface of steel slag, which reduced the wettability of the steel slag surface and significantly reduced the penetration of external moisture, thereby inhibiting the expansion of steel slag. On the other hand, the use of stearic acid alone would weaken the direct bonding effect between the modified steel slag and cement mortar, making it impossible to form a solid whole. The use of silane coupling agent as a binder for stearic acid and cement mortar improved the bonding and bite effect between the modified steel slag and cement mortar, thereby increasing the overall strength of the mixture.

[0043] Step 2: Preparation of steel slag modified by Bacillus licheniformis

[0044] The steel slag was sieved by a sieve shaker, and the stearic acid-silane coupling agent modified steel slag with a particle size of 4.75-9.5 mm was selected as the carrier material. The modified steel slag was placed in the OD 600 In the alkali-resistant Bacillus licheniformis suspension reaching 1.75, the process of immobilizing Bacillus licheniformis on modified steel slag is impregnation-vacuum-impregnation, that is, first use the excessive impregnation method for the first impregnation; put the modified steel slag carrier into the vacuum equipment, adsorb at -0.1MPa pressure, and finally perform the second impregnation, each step lasts for more than 20 minutes. After the adsorption is basically balanced, filter out the excess impregnation liquid, spread the treated modified steel slag on a shallow tray, and use a drying oven to dry it to constant weight at 25-45°C to make Bacillus licheniformis self-repairing modified steel slag particles, which are stored at room temperature for later use. It should be noted that when the modified steel slag containing the bacterial solution is dried, the temperature of the drying oven must not be too high, because excessive temperature will inactivate the bacteria.

[0045] Step 3: Preparation of recycled concrete modified by Bacillus licheniformis

[0046] Weigh the raw materials according to the following weight parts: 384 parts by weight of cement, 731.04 parts by weight of sand, 187.92 parts by weight of water, 731.28 parts by weight of 9.5-19 mm recycled aggregate, 125.76 parts by weight of 4.75-9.5 mm recycled aggregate, 240 parts by weight of Bacillus licheniformis modified steel slag, 17.83 parts by weight of calcium acetate, 48 parts by weight of aluminum oxide, and 10.16 parts by weight of urea; mix them thoroughly and stir them evenly, then pour them into a mold and vibrate them to obtain Bacillus licheniformis modified steel slag recycled concrete.

[0047] Example 2 is the same as Example 1, except that the raw materials are weighed according to the following weight parts: 300 parts by weight of cement, 700 parts by weight of sand, 150 parts by weight of water, 700 parts by weight of 9.5-19 mm recycled aggregate, 100 parts by weight of 4.75-9.5 mm recycled aggregate, 200 parts by weight of Bacillus licheniformis modified steel slag, 5 parts by weight of calcium acetate, 40 parts by weight of alumina, and 2 parts by weight of urea.

[0048] Example 3. Each raw material is weighed according to the following weight parts: 400 parts by weight of cement, 800 parts by weight of sand, 200 parts by weight of water, 800 parts by weight of 9.5-19 mm recycled aggregate, 200 parts by weight of 4.75-9.5 mm recycled aggregate, 300 parts by weight of Bacillus licheniformis modified steel slag, 20 parts by weight of calcium acetate, 50 parts by weight of alumina, and 18 parts by weight of urea.

[0049] 3. Experimental Results Analysis

[0050] 1. Optimization of mix ratio of recycled concrete modified by Bacillus subtilis

[0051] Adding a small amount of aluminum oxide to recycled concrete can reduce the high alkaline environment in the concrete, reduce the inhibition of the alkaline environment on the activity of Bacillus licheniformis, and improve its urease activity and calcium carbonate conversion efficiency. In this study, calcium acetate was selected as the nutrient supply for Bacillus licheniformis. Calcium acetate is a fast calcium ion releaser that can provide a mild and stable mineralization reaction for Bacillus licheniformis. Moreover, as the mineralization reaction of Bacillus licheniformis continues, calcium acetate can provide more calcium ions for Bacillus licheniformis. Therefore, the longer the mineralization time of Bacillus licheniformis, the more complete the reaction, and the more and more stable the mineralization products. The mineralization essence of Bacillus licheniformis is that urease catalyzes the hydrolysis of urea to produce CO3 2- ,CO3 2- Ca 2+ Combined with CaCO3. Different urea concentrations have a great influence on the mineralization efficiency of Bacillus licheniformis.

[0052] When exploring the optimal dosage of modified steel slag and alumina, the carrier of Bacillus licheniformis, in recycled concrete, it is considered that the different dosages of modified steel slag will directly affect the content of Bacillus licheniformis in the recycled concrete, thereby affecting the demand for calcium acetate and urea during the mineralization process of Bacillus licheniformis.

[0053] Based on the above reasons, this study adopts four factors and four levels L 16 (4 4 ) was used as an orthogonal test scheme to obtain the optimal mix ratios of Bacillus modified steel slag recycled concrete with modified steel slag as the carrier, as shown in Tables 4 and 5.

[0054] Table 4 Orthogonal test factors and levels

[0055]

[0056] Note: The dosage of Bacillus licheniformis modified steel slag in Table 4 / % = the weight of Bacillus licheniformis modified steel slag divided by the total weight of cement, sand, water, 9.5-19 mm recycled aggregate, 4.75-9.5 mm recycled aggregate and Bacillus licheniformis modified steel slag * 100%.

[0057] Al2O3 dosage / %=quotient of the weight of Al2O3 divided by the total weight of cement, sand, water, 9.5-19 mm recycled aggregate, 4.75-9.5 mm recycled aggregate and Bacillus licheniformis modified steel slag*100%.

[0058] Calcium acetate concentration / mol·L -1 =1000*weight of calcium acetate / (weight of water*158.17), where coefficient 158.17 is the relative molecular mass of calcium acetate.

[0059] Urea concentration / mol·L -1 =1000*urea weight / (water weight*60.06), where the coefficient 60.06 is the relative molecular mass of urea.

[0060] Table 5 Orthogonal test plan

[0061]

[0062]

[0063] From the orthogonal test data in Tables 4 and 5, it can be concluded that the content of Bacillus licheniformis modified steel slag is 20%, the content of alumina is 2%, and the content of Ca 2+ The area repair rate of recycled concrete reached the maximum when the concentration of urea was 0.6mol / L and 0.9mol / L, while the area repair rate of recycled concrete reached the maximum when the content of microbial modified steel slag was 10%, the content of alumina was 2%, and the content of Ca 2+The compressive strength of recycled concrete is the highest when the concentration is 0.6mol / L and the urea concentration is 0.9mol / L. Therefore, the best dosage is 10% steel slag and 2% alumina. The best concentration of nutrients required for mineralization of Bacillus licheniformis is 0.6mol / L calcium acetate and 0.9mol / L urea.

[0064] 2. Mechanical properties test of modified steel slag

[0065] Steel slag: Use ordinary steel slag aged for more than one year;

[0066] Stearic acid modified steel slag: Soak ordinary steel slag aged for more than one year in the prepared stearic acid solution, use a high-speed disperser to stir at a speed of 600 rad / min for 30 minutes, place it in a vacuum drying oven, and dry it at 50°C for 8 hours. After the sample is cooled to room temperature, stearic acid modified steel slag is obtained.

[0067] Silane coupling agent modified steel slag: Soak ordinary steel slag aged for more than one year in the prepared silane coupling agent solution, use a high-speed disperser to stir at a speed of 600 rad / min for 30 minutes, place it in a vacuum drying oven, and dry it at 50°C for 8 hours. After the sample is cooled to room temperature, the silane coupling agent modified steel slag is obtained.

[0068] Stearic acid-silane coupling agent modified steel slag: prepared by the method of step 1 in the specific embodiment.

[0069] 1. Water absorption rate: Referring to the specification "Test Methods for Highway Engineering Aggregates" (JTG E42-2005), the water absorption rates of various modified steel slags and ordinary steel slags were tested. The test results are as follows: Figure 1 As shown. Figure 1 It can be seen that there are significant differences in the water absorption of different types of steel slag. The water absorption rate of ordinary steel slag is the highest, about 1.7%; although stearic acid or silane coupling agent can reduce the water absorption rate of steel slag, the effect is not obvious; and the water absorption rate of steel slag modified by stearic acid and silane coupling agent is the lowest, only 0.8%, indicating that the composite modification can more effectively reduce the water absorption of steel slag while improving the bonding performance between modified steel slag and cement mortar.

[0070] 2. Water expansion rate: In order to evaluate the expansion of modified steel slag aggregate after immersion in water, the water expansion rate method was used to measure its expansion behavior according to the standard "Steel Slag Stability Test Method" (GB / T24175-2009). The test results are as follows: Figure 2 shown. Figure 2 The changes in the water absorption expansion rate of four different types of steel slag within 10 days are shown in Figure 2It can be seen that the water expansion rate of ordinary steel slag develops the fastest, and the expansion rate on the 10th day is close to 1%; the water expansion rates of stearic acid modified steel slag and silane coupling agent modified steel slag are relatively close, about 0.7% and 0.8% respectively; and the water expansion rate of stearic acid-silane coupling agent modified steel slag is the lowest, less than 0.6%, which significantly reduces the water expansion of steel slag, showing its potential in practical applications.

[0071] 3. Interface hydrophobic angle:

[0072] In order to study the hydrophilicity and hydrophobicity of the interface of steel slag aggregate before and after modification, the contact angle of steel slag aggregate before and after modification was measured using Advance-MIT 100 measuring instrument. Before each measurement, the sample was polished with sandpaper to eliminate the influence of roughness. The contact angle of the steel slag aggregate surface was measured using deionized water, and the average of the left and right contact angles was taken as the average contact angle value of the sample.

[0073] Depend on Figure 3 It can be seen that the four different types of steel slag have obvious differences in contact angle performance. Ordinary steel slag has the lowest contact angle, about 50°, indicating that its surface wettability is good; the contact angle of stearic acid modified steel slag significantly increased to about 90°, showing better hydrophobicity; the contact angle of silane coupling agent modified steel slag is slightly lower than that of stearic acid modified steel slag, about 80°, but still significantly higher than that of ordinary steel slag; and the contact angle of stearic acid-silane coupling agent modified steel slag is the highest, close to 130°, indicating that the composite modification method can significantly enhance the hydrophobicity of steel slag, making its surface almost not wetted by water.

[0074] 3. Mechanical properties test of recycled steel slag concrete modified by Bacillus licheniformis

[0075] Ordinary recycled concrete: kg / m 3 The raw material composition in units is as follows: cement 384, sand 731.04, water 187.92, 9.5-19mm recycled aggregate 731.28, 4.75-9.5mm recycled aggregate 365.76.

[0076] Bacillus licheniformis steel slag-free recycled concrete: kg / m 3 The raw material composition in units is as follows: cement 384, sand 731.04, water 187.92, Bacillus licheniformis suspension 187.92, 9.5-19mm recycled aggregate 731.28, 4.75-9.5mm recycled aggregate 365.76, calcium acetate 17.83, alumina 48, and urea 10.16.

[0077] Bacillus licheniformis modified steel slag recycled concrete: prepared from ordinary steel slag aged for more than one year.

[0078] Bacillus licheniformis unmodified steel slag recycled concrete: weigh the raw materials according to the weight parts in step 3 of Example 1, and only replace the Bacillus licheniformis modified steel slag with Bacillus licheniformis unmodified steel slag. The preparation method of Bacillus licheniformis unmodified steel slag is to replace the modified steel slag in step 2 of Example 1 with ordinary steel slag aged for more than 1 year.

[0079] 1. Unconfined compressive strength:

[0080] According to the "Concrete Physical and Mechanical Properties Test Method Standard" GB / T50081-2019, the unconfined compressive strength of recycled concrete under different working conditions was tested. During the test, the maximum load on the specimen damage was recorded, and the average value was taken as the final strength of the specimen.

[0081] The compressive strength of ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, Bacillus licheniformis unmodified steel slag recycled concrete and Bacillus licheniformis modified steel slag recycled concrete were measured at 7d, 14d and 28d. The test results are shown in Figure 4 As shown. Figure 4 It can be seen that the compressive strength of steel slag recycled concrete modified by Bacillus licheniformis at each age is higher than that of ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, and Bacillus licheniformis unmodified steel slag recycled concrete. Among them, the compressive strength of 7d Bacillus licheniformis modified recycled concrete is 28.6MPa, which is 13.5%, 9.6% and 4.8% higher than that of ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, and Bacillus licheniformis unmodified steel slag recycled concrete, respectively. With the increase of age, the strength of 14d Bacillus licheniformis modified steel slag recycled concrete reaches 34.1MPa, which is 14.4%, 8.6% and 4.9% higher than that of ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, and Bacillus licheniformis unmodified steel slag recycled concrete, respectively. After 28 days of curing, the compressive strength of the steel slag recycled concrete modified by Bacillus licheniformis was 42.3MPa, which was 28.6%, 19.1% and 11.0% higher than that of the ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, and Bacillus licheniformis unmodified steel slag recycled concrete, respectively. It can be seen that the synergistic effect of Bacillus licheniformis and modified steel slag significantly improved the unconfined compressive strength of recycled concrete.

[0082] 2. Splitting tensile strength:

[0083] According to the "Concrete Physical and Mechanical Properties Test Method Standard" GB / T50081-2019, the splitting tensile strength of recycled concrete under different working conditions was tested. During the test, the maximum load on the specimen damage was recorded, and the average value was taken as the final strength of the specimen.

[0084] The 7d and 28d tensile strengths of ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, Bacillus licheniformis unmodified steel slag recycled concrete and Bacillus licheniformis modified steel slag recycled concrete were measured respectively. The test results are shown in Figure 5 As shown. Figure 5 It can be seen that the tensile strength of steel slag recycled concrete modified by Bacillus licheniformis at each age is higher than that of ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, and Bacillus licheniformis unmodified steel slag recycled concrete. Among them, the tensile strength of 7d Bacillus licheniformis modified steel slag recycled concrete is 2.6MPa, which is 30%, 18.2% and 6.1% higher than that of ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, and Bacillus licheniformis unmodified steel slag recycled concrete, respectively. With the increase of age, the tensile strength of 28d Bacillus licheniformis modified steel slag recycled concrete is 3.62MPa, which is 38.7%, 23.5% and 7.4% higher than that of ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, and Bacillus licheniformis unmodified steel slag recycled concrete, respectively. It can be seen that the synergistic effect of Bacillus licheniformis and modified steel slag significantly improves the splitting tensile strength of recycled concrete.

[0085] 4. Porosity distribution:

[0086] BET tests were performed on 7d and 28d old ordinary recycled concrete, Bacillus licheniformis recycled concrete without steel slag, Bacillus licheniformis unmodified steel slag recycled concrete and Bacillus licheniformis modified steel slag recycled concrete using an automatic gas adsorption analyzer model ASAP2020HD88. Before the measurement, the samples were degassed at 150°C for 4 hours under vacuum conditions to remove any adsorbed moisture or volatile compounds. After degassing, the samples were exposed to nitrogen at liquid nitrogen temperature (-196°C) for adsorption. Nitrogen adsorption-desorption isotherms were obtained by measuring nitrogen adsorption values ​​at different relative pressures P / P0 (P0 represents the nitrogen adsorption saturation pressure and P represents the nitrogen adsorption equilibrium pressure), and the specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method. The pore size distribution was obtained from the isotherm data using the BJH (Barrett-Joyner-Halenda) method.

[0087] Depend on Figure 6It can be seen that the pore volume of ordinary recycled concrete at 7d and 28d decreases with the increase of pore size, and the pore volume of 28d is generally lower than that of 7d, indicating that the pore structure has improved over time. However, the overall pore volume is still high. The pore volume of Bacillus licheniformis modified steel slag recycled concrete is the lowest at 7d and 28d, and the trend of decreasing with the increase of pore size is the most obvious, indicating that the pore structure is effectively optimized after the composite action of Bacillus licheniformis and modified steel slag. Compared with other types, the pore volume of Bacillus licheniformis modified steel slag recycled concrete is the lowest at all pore sizes, showing the best pore structure. The trend of the pore volume of Bacillus licheniformis steel slag recycled concrete decreasing with the increase of pore size is similar to that of ordinary recycled concrete, but the overall pore volume is slightly lower, indicating that Bacillus licheniformis alone also has a certain optimization effect, but compared with Bacillus licheniformis modified steel slag recycled concrete, its pore structure still has a gap. The trend of the pore volume of the unmodified steel slag recycled concrete decreasing with the increase of pore size is between that of the steel slag recycled concrete modified by Bacillus licheniformis and that of the steel slag recycled concrete without Bacillus licheniformis, indicating that the composite action of Bacillus licheniformis and unmodified steel slag also improves the pore structure to a certain extent, but its effect is not as obvious as that of the steel slag recycled concrete modified by Bacillus licheniformis. In general, the steel slag modified by Bacillus licheniformis significantly reduces the pore volume of the recycled concrete, improves the pore structure, and increases the density of the recycled concrete. At the same time, this modification technology performs better in the later stage of curing.

[0088] The above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by a person skilled in the art within the spirit and scope of the present invention shall also fall within the protection scope of the present invention.

Claims

1. A method for preparing steel slag modified by Bacillus licheniformis, characterized in that The following steps are involved: Step 1: Preparation of modified steel slag The steel slag is immersed in a stearic acid solution, stirred at a speed of 400-800 rad / min for 20-40 minutes by a high-speed disperser, and then placed in a vacuum drying oven at 45-55° C. for 6-10 hours. After the sample is cooled to room temperature, it is further immersed in a silane coupling agent solution, stirred at a speed of 400-800 rad / min for 20-40 minutes by a high-speed disperser again, and then placed in a vacuum drying oven at 45-55° C. for 6-10 hours to obtain a modified steel slag; Step 2: Preparation of steel slag modified by Bacillus licheniformis The modified steel slag obtained in the step is sieved by a shaking screen to select the modified steel slag with a particle size of 4.75-9.5 mm as a carrier material, immersed in a Bacillus licheniformis suspension for 20-60 minutes, taken out and placed in a vacuum machine for vacuuming, adsorbed at a pressure of -0.1 MPa for 20-60 minutes, immersed in the Bacillus licheniformis suspension for 20-60 minutes, and then filtered to remove excess impregnation liquid, and dried at 25-45° C. to constant weight to obtain Bacillus licheniformis modified steel slag.

2. The method for preparing steel slag modified by Bacillus licheniformis according to claim 1, characterized in that The preparation method of the stearic acid solution is as follows: add stearic acid into ethanol, and stir evenly at 400-600 rpm at 40-50° C. using a magnetic stirrer to obtain a stearic acid solution with a mass concentration of 1%.

3. The method for preparing steel slag modified by Bacillus licheniformis according to claim 1, characterized in that The preparation method of the silane coupling agent solution is as follows: after mixing the silane coupling agent, water and ethanol in a volume ratio of 3:47:50, stirring at a speed of 100-300 rpm for 30-60 minutes at room temperature until the solution is transparent without obvious particles or precipitation, the silane coupling agent solution is obtained.

4. The method for preparing steel slag modified by Bacillus licheniformis according to claim 1, characterized in that The preparation method of the Bacillus licheniformis suspension is as follows: transfer the freeze-dried powder of Bacillus licheniformis into a solid culture medium for activation, select the activated strain and inoculate it into a liquid culture medium, culture it in a constant temperature shaking incubator at 25-35°C, culture it for 20-28h, pH value is 7-11, inoculation amount is 4% by volume, when the OD of the strain in the culture medium is 600 When the value reaches 1.75, Bacillus licheniformis suspension is obtained.

5. The method for preparing steel slag modified by Bacillus licheniformis according to claim 4, characterized in that: The solid culture medium is prepared by dissolving 10 g of peptone, 5 g of sodium chloride, 3 g of beef extract and 20 g of agar in 1 L of distilled water, sterilizing in an autoclave at 121° C. and adjusting the pH to 10-12 with a Na(OH)2 solution. The liquid culture medium is prepared by dissolving 10 g of peptone, 5 g of sodium chloride and 3 g of beef extract in 1 L of distilled water and sterilizing in an autoclave at 121° C.

6. A Bacillus licheniformis modified steel slag recycled concrete obtained by using the preparation method according to any one of claims 1 to 5, characterized in that The invention is composed of the following raw materials and their weight proportions: 300-400 weight parts of cement, 700-800 weight parts of sand, 150-200 weight parts of water, 700-800 weight parts of 9.5-19 mm recycled aggregate, 100-200 weight parts of 4.75-9.5 mm recycled aggregate, 200-300 weight parts of steel slag modified by Bacillus licheniformis, 5-20 weight parts of calcium acetate, 40-50 weight parts of aluminum oxide and 2-18 weight parts of urea.

7. The Bacillus licheniformis modified steel slag recycled concrete according to claim 6, characterized in that The invention is composed of the following raw materials and their weight proportions: 384 weight parts of cement, 731.04 weight parts of sand, 187.92 weight parts of water, 731.28 weight parts of 9.5-19 mm recycled aggregate, 125.76 weight parts of 4.75-9.5 mm recycled aggregate, 240 weight parts of Bacillus licheniformis modified steel slag, 17.83 weight parts of calcium acetate, 48 weight parts of aluminum oxide and 10.16 weight parts of urea.